INTERACTIVE LEARNING VIA DIGITAL STORYTELLING IN ELT AT ELEMENTARY SCHOOL : SYSTEMATIC REVIEW - Setyawati, Vita Rahayu (Universitas Lambung Mangkurat, 2023)
Abstract: In 4.0 era, digitalization in ELT at elementary school can be a complex learning tool. As we know that ICT facilitated and expanded access to education. One of the media using ICT in ELT is DS (Digital Storytelling). DS (Digital Storytelling) that is a story which narrate by using the digital multimedia such as: the video and the image. This study aims to analyse interactive learning via DS (Digital Storytelling) in ELT at elementary school. To understand kinds of the research studies that related to DS (Digital Storytelling), the writer used SLR (Systematic Literature Review) The research found through Google Scholar, Semantic Scholar, Pubmed, and Crossref from 2020-2023. This study executed in accordance 6 research articles consists of National Journal and International Journal. The result of this study showed that qualitative method research was the most popular research design. The result of this study that has been carried out that there are advantages applying DS (Digital Story telling) in interactive learning in ELT at the elementary school such as : it can improve the speaking skill, writing skill, reading skill, and listening skill, it can improve the students’ motivate and the students’ engagement, it can increase the levels of the students’ interactions and the students’ collaboration, it can improve the students’ collaboration, the students’ creativity skills, the students’ critical thinking. The innovation is needed to help teacher improve the quality of learning in elementary school. It promotes better understanding for the content and curricula for the educators. Keywords: Digital Storytelling, Interactive Learning, ELT, Elementary School